Altered carnitine-acylcarnitine profiles in levothyroxine-treated congenital hypothyroid patients with fatigue: An LC-MS/MS-based study from Bangladesh - Mst. Noorjahan Begum; Suprovath Kumar Sarker; Md Tarikul Islam; Golam Sarower Bhuyan; Rumana Mahtarin; Mohammad Hridoy Patwary; Tasnia Kawsar Konika; Syeda Kashfi Qadri; Tasnuva Ahmed; Hurjahan Banu; Nusrat Sultana; Asifuzzaman Rahat; et al. (PLoS ONE, 2025)
Congenital hypothyroidism (CH), characterized by insufficient thyroid hormone production at birth, is frequently associated with fatigue, particularly in cases with delayed diagnosis. This study employed liquid chromatography–tandem mass spectrometry (LC-MS/MS) to profile carnitine and acylcarnitines in late-diagnosed congenital hypothyroid patients receiving levothyroxine (LT4) therapy, with the aim of identifying metabolic alterations that may be associated with fatigue symptoms. A total of 56 late-diagnosed congenital hypothyroid patients and 107 age-, sex-, and BMI-matched healthy controls were enrolled. Blood samples were collected in EDTA tubes and as dried blood spots (DBS) on Whatman® 903 filter paper. LC-MS/MS was used to quantify free carnitine and 28 acylcarnitines, and plasma triglyceride (TG) levels were measured using a biochemical analyzer. Compared to healthy controls, congenital hypothyroid patients showed higher mean (±SD) concentrations of free carnitine (45.38 ± 12.61 vs. 41.54 ± 9.85 µmol/L; P = 0.049), total carnitines (67.33 ± 18.27 vs. 62.51 ± 14.13 µmol/L), and total acylcarnitines (21.95 ± 7.66 vs. 20.96 ± 5.61 µmol/L), although only free carnitine levels were statistically significant. Long-chain acylcarnitines were significantly lower in congenital hypothyroid patients (2.67 ± 0.87 µmol/L) compared to controls (3.15 ± 0.93 µmol/L; P = 0.0014). The β-oxidation ratio C0/(C16 + C18), a proxy for Carnitine Palmitoyltransferase I (CPT-I) activity, was significantly elevated in patients compared to healthy controls (34.55 ± 14.88 vs. 25.73 ± 6.87; P < 0.0001). Plasma TG levels were also significantly higher in patients (88.92 ± 59.54 mg/dL) than in controls (58.33 ± 15.79 mg/dL; P = 0.02). Metabolic profiling in congenital hypothyroid patients revealed impaired long-chain fatty acid oxidation and elevated triglyceride levels. These metabolic changes may contribute to fatigue symptoms and are potentially associated with reduced CPT-I activity, which is essential for mitochondrial β-oxidation. Additionally, mutations in the TPO and TSHR genes identified within this cohort may be linked to the observed metabolic alterations. Collectively, these findings suggest a possible interplay between genetic variants, disrupted lipid metabolism, and clinical features of congenital hypothyroidism.